Peranan Pendidikan Agama Islam dalam Memotivasi Anak untuk Beribadah di MtsS Yati Kamang Mudiak - Aulia Rahmi Shakila; Ulva Rahmi; Delvianti Delvianti; Andy Riski Pratama (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
People who hold a position in society are expected to exhibit certain behaviors, or roles. In Islamic religious education, the teacher's job is to teach students how to develop into morally upright people. Islamic religious education is a form of education that imparts knowledge while also molding students' attitudes, personalities, and talents. Researchers employed a qualitative and descriptive technique in this investigation. This is so that information can be provided as simply as possible. The research seeks to describe the reality that exists without needing data in the form of numbers (quantitative), and it tries to describe a scenario and all of its components. researchers think is feasible. The goal of this study is to comprehend the situation or circumstances that exist in MTsS YATI KAMANG MUDIAK, where the worship services were held.